The queen of the damned eaudiobook - Rice, Anne (The Vampire Chronicles, 2011)
In a feat of virtuoso storytelling, Anne Rice unleashes Akasha, the queen of the damned, who has risen from a six-thousand-year sleep to let loose the powers of the night. Akasha has a marvelously devious plan to “save” mankind and destroy the vampire Lestat—in this extraordinarily sensual novel of the complex, erotic, electrifying world of the undead.   Praise for The Queen of the Damned   “Mesmerizing . . . a wonderful web of dark-side mythology.” — San Francisco Chronicle   “With The Queen of the Damned, Anne Rice has created universes within universes, traveling back in time as far as ancient, pre-pyramidic Egypt and journeying from the frozen mountain peaks of Nepal to the crowded, sweating streets of southern Florida.” — Los Angeles Times   “Imaginative . . . intelligently written . . . This is popular fiction of the highest order.” — USA Today   “A tour de force.” —The Boston Globe